Needle and syringe programmes in the local media: “needle anger” versus “effective education in the community” - Körner, Henrike; Treloar, Carla (The International journal of drug policy, 2004)
The Australian National Council on Drugs (ANCD) recently recommended that media organisations commit to balanced and accurate reporting about the costs and benefits of needle and syringe programmes (NSPs), and recognise the harm of sensationalist reporting. This paper is concerned with the newspaper reporting of syringes found in or near a Sydney primary school, which resulted in the closure of the nearby NSP. Four news reports, one editorial and two letters to the editor in three regional papers dealt with this issue. We examined the intertextual links between and within texts: which speaking subjects are included, whose messages are foregrounded or backgrounded, how are these messages represented by the reporters, and how are alternative positions negotiated. Our analysis shows that in spite of an absence of overt judgements and sensationalism by the reporters, representations are not value free. Choices made by the writers of news reports show alignment with various convergent and divergent positions relating to NSPs in general and the closure of this needle exchange in particular.